A Penny for Your Thoughts: Properties of Anthropology in a Transnational Present - Robertson, Leslie (Anthropologica, 2022)
Fieldworkers, and the materials we construct, are situated at a complex intersection of colliding interests. We negotiate agreements of access and use of "information" with individuals, and community, national or transnational authorities. Universities and funding agencies impose sanctions governing the ownership of collected materials and disciplinary tradition provides an ethical universe within which we practice. Finally, fieldworkers are subject to federal and provincial laws, and are thus implicated in the larger controversy of intellectual and cultural property. Through the elicited opinions of field workers I explore the tensions of access, use and ownership of "data" with particular attention to the ownership of field notes.